Age, health and other factors associated with return to work for those engaging with a welfare-to-work initiative: a cohort study of administrative data from the UK's Work Programme. Issue 10 (27th October 2018) - Brown, Judith; Katikireddi, Srinivasa Vittal; Leyland, Alastair H; McQuaid, Ronald W; Frank, John; Macdonald, Ewan B
Abstract : Objectives: To investigate the role of individual factors (including age, health and personal circumstances) and external factors associated with clients having a job start while engaging with the Work Programme and variations by benefit type. Setting: The UK Government's main return to work initiative (The Work Programme) in Scotland. Design: Piecewise Poisson regression to calculate incident rate ratios using administrative data from 2013 to 2016 to identify factors associated with job start. Participants: 4322 Employment and Support Allowance (ESA) clients not in work due to poor health and 8996 Jobseeker's Allowance (JSA) clients, aged 18–64 years, referred to the Work Programme between April 2013 and July 2014. Main outcome measures: Starting a job and the time to first job start after entering the Work Programme. Results: JSA clients (62%) were more likely to return to work (RTW) than ESA clients (20%). There is a strong negative relationship between age and the predicted probability of having a job start during the 2-year engagement with the programme for both JSA and ESA clients. JSA clients were most likely to RTW in the first 3 months, while for ESA clients the predicted probability of having a first job start was fairly constant over the 2 years. Health, including the number of health conditions, length of unemployment, client perception of job start and other individual factors were associated with job starts for both groups. Conclusions: Age plays an important role in influencing RTW; however, important potentially modifiable factors include the length of unemployment, the management of multimorbidity and the individual's perception of the likelihood of job start. Future welfare-to-work programmes may be improved by providing age-specific interventions which focus on health and biopsychosocial factors to enable more people to realise the potential health benefits of RTW.